Luminescence Mechanism in Amorphous Silicon Oxynitride Films: Band Tail Model or N-Si-O Bond Defects Model - Chen, Kunji; Lin, Zewen; Zhang, Pengzhan; Huang, Rui; Dong, Hengping; Huang, Xinfan (Frontiers in Physics, 2019)
Silicon oxynitride films are one kind of important gate dielectric materials for applications in the fabrication of silicon CMOS integrated circuits (ICs), which have been widely and deeply studied. However, with the significant demand of the technologies for Si-based monolithic optoelectronic ICs, the research efforts on the optoelectronic applications of these materials have been continually increasing, particularly in the study of light emission properties and recombination mechanisms. In this paper, we first briefly outline the present photoluminescence (PL) mechanisms in amorphous silicon oxynitride (a-SiOxNy) films. Since the PL properties and recombination processes are affected by both structural disorder and chemical disorder, the PL mechanism has been still unclear and even controversial until now. Among these various PL recombination models, the band tail states and defect states models have gained general consensus. Recently a N-Si-O bond defect model has been reported, which depends on relative atom concentration of oxygen and nitrogen in the silicon oxynitride materials. It has been revealed that oxygen bonding plays a key role not only in reducing the structural disorder, but also in creating N-Si-O (Nx) defect states in the band gap. The characteristics of two models, namely band tail and N-Si-O bond defects, have been discussed in detail. Finally it has been shown that by controlling the chemical composition of these non-stoichiometric silicon oxynitride materials, the optical and electronic properties can be improved.